HUBUNGAN PENGETAHUAN PENGOLAHAN MAKANAN DENGAN KETERAMPILAN MENGOLAH MAKANAN INDONESIA PADA SISWA SEKOLAH MENENGAH KEJURUAN - Nurul Ridhi Utami (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2018)
The objectives of this study are to determine theknowledge of learners of food processing, skills of learners toprocess Indonesian food, the relationship of food processingknowledge with the skills of processing food Indonesia. Thisstudy includes ex post facto research. Instrument result datatested validity and reliability, data analysis technique usingProduct Moment correlation. The results showed that theknowledge of food processing in sufficient category, theskills of processing Indonesian food in the category enough,there is a positive relationship and significant knowledgeof food processing with food processing skills of Indonesia.The determinant coefficient (RÂ²) is 0.283, meaningthat the contribution given by food processing knowledgeto Indonesian food processing skill is 28.3%, while theremaining 71.7% is influenced by other factors.